Factors Increasing Loyalty of Local Cosmetic Brands: A Study on Generation Z in Indonesia - Suwandi, Dita Sari; Balqiah, Tengku Ezni (Binus Business Review, 2023)
Competition in the beauty industry in Indonesia raises problem of loyalty with various choices and information accessibility from the Internet. Issues also surface from Generation Z, recently reported to dominate the market as digitally savvy and tends to be disloyal to one brand. The research aimed to analyze the factors that increased brand loyalty in the local cosmetics industry, specifically from Generation Z in Indonesia, through brand love and the mediation effects of self-esteem, susceptibility to normative influence, and social media brand engagement. The research applied a quantitative approach by distributing online questionnaires and purposive sampling to 321 respondents. The data obtained were processed with Structural Equation Modeling (SEM) with Partial Least Square approach (PLS) using SmartPLS. The results show a direct relationship between brand love and brand loyalty, brand love with the mediating variables (self-esteem, susceptibility to normative influence, and social media brand engagement), and two dimensions of social media brand engagement (affective and behavioral social media brand engagement) with brand loyalty. The other two mediating variables, such as self-esteem and susceptibility to normative influence and behavioral social media brand engagement, do not affect brand loyalty. However, the mediating effect only exists through affective and behavioral dimensions in increasing brand love relationships with brand loyalty. The research contributes to Indonesia’s business practitioners retaining their consumers amid intense competition by utilizing affective and behavioral factors in giving information on social media.